State-dependent modulation of feeding behavior by proopiomelanocortin-derived β-endorphin - Low, Malcolm J. (2003)
Feeding behavior can be divided into appetitive and consummatory phases, differing in neural substrates and effects of deprivation. Opioids play an important role in the appetitive aspects of feeding, but they also have acute stimulatory effects on food consumption. Because the opioid peptide β-endorphin is co-synthesized and released with melanocortins from proopiomelanocortin (POMC) neuronal terminals, we examined the physiological role of β-endorphin in feeding and energy homeostasis using a strain of mutant mice with a selective deficiency of β-endorphin. Male β-endorphin-deficient mice unexpectedly became obese with ad libitum access to rodent chow. Total body weight increased by 15% with a 50-100% increase in the mass of white fat. The mice were hyperphagic with a normal metabolic rate. Despite the absence of endogenous β-endorphin, the mutant mice did not differ from wild-type mice in their acute feeding responses to β-endorphin or neuropeptide Y administered intracerebroventricularly or naloxone administered intraperitoneally. Additional mice were studied using an operant behavioral paradigm to examine their acquisition of food reinforcers under increasing work demands. Food-deprived, β-endorphin-deficient male mice emitted the same number of lever presses under a progressive ratio schedule compared to wild-type mice. However, the mutant mice worked significantly less than did the wild-type mice for food reinforcers under nondeprived conditions. Controls for nonspecific effects on acquisition of conditioned learning, activity, satiety, and resistance to extinction revealed no genotype differences, supporting our interpretation that β-endorphin selectively affects a motivational component of reward behavior under nondeprived conditions. Therefore, we propose that β-endorphin may function in at least two primary modes to modulate feeding. In the appetitive phase, β-endorphin release increases the incentive value of food as a primary reinforcer. In contrast, it appears that endogenous β-endorphin may inhibit food consumption in parallel with melanocortins and that the orexigenic properties previously ascribed to it may actually be due to other classes of endogenous opioid peptides.